Ensuring the effectiveness and safety of peripheral blockades - I. G. Oleshchenko; D. V. Zabolotsky; V. A. Koriachkin; V. V. Pogorelchuk (Acta Biomedica Scientifica)
Adequate analgesia determines the success of the performed surgical intervention. In modern surgery, most of postoperative complications are directly related to ineffective therapy of pain syndrome in the perioperative period. The main principle of modern analgesia is its multicomponence, when analgesia, neurovegetative blockade and relaxation are achieved and potentiated by different drugs and methods. The blockade of nociceptive impulses with a local anesthetic at the transmission stage provides effective, targeted analgesia, hyporefl exia and muscle relaxation, prevents the sensitization of neuroaxial structures, hyperalgesia and the development of postoperative chronic pain syndrome. At the same time, providing analgesia with drugs of central action leads to the ineffectiveness of therapy in 80 % of cases, which has serious consequences.The aim. According to the literature review, to evaluate the effectiveness and safety of peripheral blockades on the example of performing a blockade of the pterygopalatine ganglion.Conclusion. The pterygopalatine blockade has broad indications for use in ophthalmology, which is explained by the complex structure of the pterygopalatine ganglion and the possibility of simultaneous infl uence on sympathetic, parasympathetic and nociceptive innervation. All the presented methods of pterygopalatine blockade performance have their advantages and disadvantages. Ultrasound navigation eliminates technical difficulties and the possibility of damage of the pterygopalatine fossa anatomical structures, ensuring the effectiveness and safety of the pterygopalatine blockade.